1999
DOI: 10.1001/archopht.117.10.1384
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Macular Degeneration and Antioxidant Status in the POLA Study

Abstract: To give the levels of antioxidant nutrients in relation to age-related macular degeneration (AMD). Methods: Pathologies Oculaires Liées à l'Age is a population-based study on cataract and AMD and their risk factors, carried out on 2584 inhabitants of Sète, France. Age-related macular degeneration was defined by findings from fundus photographs according to an international classification. Biological measurements were taken from fasting blood samples. Results: After multivariate adjustment, plasma ␣-tocopherol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
11

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(114 citation statements)
references
References 38 publications
(25 reference statements)
6
97
0
11
Order By: Relevance
“…Lutein was chosen as the antioxidant to compete with a-tocopherol for absorption because both vitamin E and lutein supplements are becoming increasingly popular owing to their potential ability to prevent agerelated macular degeneration (Belda et al, 1999;Delcourt et al, 1999;Mares-Perlman et al, 2001;Olmedilla et al, 2003;Richer et al, 2004). Data from the clinical study suggest that increasing dietary lutein from 18 to 36 mg reduces a-tocopherol absorption (area under the curve (AUC) down by 38%).…”
Section: Discussionmentioning
confidence: 99%
“…Lutein was chosen as the antioxidant to compete with a-tocopherol for absorption because both vitamin E and lutein supplements are becoming increasingly popular owing to their potential ability to prevent agerelated macular degeneration (Belda et al, 1999;Delcourt et al, 1999;Mares-Perlman et al, 2001;Olmedilla et al, 2003;Richer et al, 2004). Data from the clinical study suggest that increasing dietary lutein from 18 to 36 mg reduces a-tocopherol absorption (area under the curve (AUC) down by 38%).…”
Section: Discussionmentioning
confidence: 99%
“…Initial epidemiological observations, showing that high vitamin E plasma levels may protect against AMD [4], have been confirmed by a large randomised clinical trial performed in the United States. In this study, performed on nearly 5,000 subjects, supplementation for 6 years with high doses of antioxidants (vitamin E, C and beta-carotene) and zinc significantly reduced by 34 % the risk of developing advanced AMD in subjects with early AMD [5].…”
mentioning
confidence: 84%
“…Data from the National Health and Nutrition Examination Survey, reported by Goldberg et al, showed a negative association between the frequency of fruit and vegetables rich in vitamin A consumed and the prevalence of AMD [16]. However, several subsequent studies and a large metaanalysis failed to confirm this association [20,22,39,40], and unexpectedly, one report even suggested an increased risk in the development of late AMD in participants who took vitamin A [41]. With these conflicting results, more research is needed regarding the association between vitamin A and AMD.…”
Section: Vitamin Amentioning
confidence: 99%
“…Although there was no association found between vitamin E and AMD in the Eye Disease Case-Control Study [17], in the POLA (Pathologies Oculaires Liées à l'Age) study by Delcourt et al, a reduction in the risk of late AMD in individuals with enhanced plasma levels of alpha-tocopherol was demonstrated [39]. Several studies report a weak or non-existent association between alpha-tocopherol levels/vitamin E supplements and the risk of AMD [33,45].…”
Section: Vitamin Ementioning
confidence: 99%
See 1 more Smart Citation